Clinical significance of detectable and quantifiable HCV RNA at the end of treatment with ledipasvir/sofosbuvir in GT1 patients. (10th August 2018) - Maasoumy, Benjamin; Buggisch, Peter; Mauss, Stefan; Boeker, Klaus H. W.; Müller, Tobias; Günther, Rainer; Zimmermann, Tim; Manns, Michael P.; Sarrazin, Christoph; Hüppe, Dietrich; Wedemeyer, Heiner; Vermehren, Johannes
Abstract: Background & Aims: AASLD/IDSA treatment guidelines for hepatitis C virus (HCV) infection state that testing for quantitative HCV RNA can be considered at the end of antiviral treatment (EOT) with interferon‐free regimens. However, it remains unclear how to respond to a detectable or even quantifiable HCV RNA result. The aim of this study was to analyse the frequency and predictive value of detectable and quantifiable HCV RNA results at the EOT in patients with HCV genotype 1 infection treated with ledipasvir (LDV) and sofosbuvir (SOF) ± ribavirin (RBV) in a large real‐world cohort. Methods: A retrospective analysis of the DHC‐R (Deutsches Hepatitis C‐Register, German Hepatitis C‐Registry) cohort was performed including all patients who were treated with LDV/SOF ± RBV and in whom HCV RNA testing was done with either the Roche COBAS AmpliPrep/COBAS TaqMan (CAP/CTM) or the Abbott RealTime HCV assay (ART). Results: The frequency of detectable HCV RNA at the EOT was 7% in this real‐world study involving 471 patients. Furthermore, 3% of the patients (n = 14/471) even had quantifiable viral load at the EOT. Detectable and quantifiable results were more frequent if the ART was used for testing. However, SVR was achieved by 32/33 patients (97%) with detectable and even by all 14 patients (100%) with quantifiable HCV RNA results at the EOT. Conclusion: Detectable and even quantifiable HCV RNA results are quite frequent if highly sensitive HCV RNA assays are used. However, treatment prolongation is not indicated, as SVR rates remain high in these patients.